2019
DOI: 10.22616/foodbalt.2019.035
|View full text |Cite
|
Sign up to set email alerts
|

The optimization of acid whey permeate hydrolysis for glucose-galactose syrup production

Abstract: Whey contains a lot of lactose, which can be easily hydrolysed by commercial enzymes. The aim of the present study was to identify the optimal parameters for the enzymatic hydrolysis of acid whey permeate and glucose-galactose syrup production. Acid whey permeate was hydrolysed using β-galactosidase preparate (NOLA TM Fit 5500, Chr. Hansen, Denmark) with activity 7200 BLU L -1 . As the enzyme is strongly inhibited at pH below 4.5, sodium bicarbonate was added to neutralize substrate pH till 6.0-6.3. The hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The literature reports present various examples of β-galactosidase immobilisation. Among them, κ-carrageenan beads [28], chitosan-hydroxyapatite beads [29], fibres composed of alginate and gelatin hardened with glutaraldehyde [30], cellulose acetate-polymethylmethacrylate membrane [31], and glass beads [32] have been proposed. The utilisation of sodium alginate in the dairy industry context is justified due to the natural source of the main compound and mild gelation conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature reports present various examples of β-galactosidase immobilisation. Among them, κ-carrageenan beads [28], chitosan-hydroxyapatite beads [29], fibres composed of alginate and gelatin hardened with glutaraldehyde [30], cellulose acetate-polymethylmethacrylate membrane [31], and glass beads [32] have been proposed. The utilisation of sodium alginate in the dairy industry context is justified due to the natural source of the main compound and mild gelation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The last cycle time should be extended to about 4 h. These results are satisfactory, especially in the case of temperature value during lactose conversion, 15 • C, which corresponds to the temperature of milk transportation and storage. For comparison, acid whey bioconversion catalysed by NOLA can last even 2 h at 40 • C [28].…”
Section: Discussionmentioning
confidence: 99%
“…Chiu and Kosikowski (1985) made a 100% hydrolyzed syrup at 60% solids and successfully stored it for 4 weeks at room temperature without any crystallization issues. Samadov et al (2019) recommend concentrating syrups to 65% total solids to achieve optimal sweetness and maintain storage stability. There are two primary methods used to create these syrups in the food industry, using either enzymes or acids.…”
Section: Hydrolyzed Syrupsmentioning
confidence: 99%
“…In an early study by Chiu and Kosikowski (1985), the authors successfully created a sweet, almost colorless syrup from a sweet WP using yeast lactase, which was decolorized by addition of 0.2% activated carbon, filtered, and concentrated to 60% solids under vacuum. More recently, Samadov et al (2019) investigated the production of a glucose-galactose syrup from an acid WP and successfully hydrolyzed all of the lactose after only 2 h of fermentation using β-galactosidase at 40 • C. Majore and Ciprovica (2022) investigated the production of a glucose-galactose syrup with increased sweetness and an improved sugar profile from sweet or acid permeate by carrying out a second enzymatic bioconversion step after hydrolysis, in order to convert some of the glucose into fructose using immobilized glucose isomerase. Results demonstrated that fructose yields were higher in sweet WP (∼20%) compared to acid WP (∼10%), which is likely due to the higher calcium ion concentration in acid whey inhibiting glucose isomerase activity.…”
Section: Hydrolyzed Syrupsmentioning
confidence: 99%
“…After some period of time the amount of glucose and galactose in each substrate changes and is no longer equimolar (1:1). The conversion factor for the forming lactose into glucose and galactose ranged from 1.05 to 1.11 (Samadov et al, 2019). Which means that the β-galactosidase starts to produce galacto-oligosaccharides under certain conditions (Mariyani et al, 2015).…”
mentioning
confidence: 99%